Analysis of Factors Causing Delays in the Diesel Engine Remanufacturing Process at an Indonesian Company - Erwin Soeseno; Ratih Dyah Kusumastuti (Logistics, 2018)
HeavyEq is an Indonesian company that remanufactures diesel engines for the mining industry. The company experiences delays in the remanufacturing process that lead to a sales backlog. The main purpose of this paper is to identify the root cause of, and propose a solution to, the problem. A fishbone diagram is developed to identify the root cause, and the results show that delays in the remanufacturing process are mainly caused by uncertainty over cores (used engines) in terms of their arrival time, quantity, and quality. Based on a literature review and interviews with experts, an improvement in core acquisition activity, separating job orders for disassembly and recovery, and reassembly processes is proposed to reduce delays in the remanufacturing process.